Characteristics of the Pedagogical System for Developing the Educational Potential of the Academy Cadets in Studying Military English - Solyakhova L.R. (Zien Journals, 2022)
In this article, the characteristics of the pedagogical system for the development of educational potential on the basis of competence among cadets of the academy in the study of military English are considered and studied.
Keywords: pedagogical system; competencies; English language; cadets